Wicked bugs : the louse that conquered Napoleon's army & other diabolical insects - Stewart, Amy.; Morrow-Cribbs, Briony (Chapel Hill, N.C. : Algonquin Books of Chapel Hill, 2011)
In this darkly comical look at the sinister side of our relationship with the natural world, Stewart has tracked down over one hundred of our worst entomological foes-creatures that infest, infect, and generally wreak havoc on human affairs.
In this darkly comical look at the sinister side of our relationship with the natural world, Stewart has tracked down over one hundred of our worst entomological foes-creatures that infest, infect, and generally wreak havoc on human affairs.
African bat bug -- She's just not that into you -- Asian giant hornet -- Assassin bug -- Bugs of war -- Bed bug -- Biting midge -- Black fly -- Black widow -- Stinging caterpillars -- Bombardier beetle -- Brazilian wandering spider -- Curse of the scorpion -- Brown marmorated stink bug -- Brown recluse -- Chigger mite -- Chigoe flea -- Have no fear -- Cockroach -- Colorado potato beetle -- The gardener's dirty dozen -- Corn rootworm -- Death-watch beetle -- Bookworms -- Deer tick -- Filth fly -- I've got you under my skin -- Formosan subterranean termite -- The ants go marching -- Giant centipede -- Mediterranean fruit fly -- Millipede -- Arrow poisons -- Mosquito -- Mountain pine beetle -- Nightcrawler -- The enemy within -- Oriental rat flea -- Paederus beetle -- Corpse-eaters -- Phylloxera -- Rocky Mountain locust -- Fear no weevils -- Sand fly -- Scabies mite -- What's eating you? -- Spanish fly -- Tarantula -- Tsetse fly -- Zombies.
Includes bibliographical references and index.
Requires Adobe Digital Editions (file size: 6646 KB).
Keywords: Insect pests; Arachnida; Electronic books